Pengembangan Media Pembelajaran Geografi Berbasis Aplikasi Classdojo Pada Materi Adaptasi Dan Mitigasi Bencana Di Kelas Xi SMA Negeri 1 Tilango - Abas, Fatma D; Maryati, Sri; Yusuf, Daud (Universitas Negeri Gorontalo, 2024)
Research and development of learning media based on the Classdojo application was developed on Disaster Adaptation and Mitigation material. The purpose of this research is to develop geography learning media based on Classdojo application on disaster adaptation and mitigation material in class XI SMA Negeri 1 Tilango. The method used in this research is research and development (RD) type ADDIE. The results of the feasibility of the products developed using validation questionnaires from media experts, material experts and geography teacher learning experts, limited and general tests were analyzed from the results of student responses before and after the use of Classdojo application-based geography learning media. The results showed the results of the level of validity of media experts with a percentage of 83.3% (very valid category), material experts after revision with a percentage of 87.6% (very valid category), geography teachers with a percentage of 90.7% (very valid category). geography teacher with a percentage of 90.7% (category very valid). Student responses on a limited scale trial got an average percentage of 82.17%. The general scale test results get an average percentage of 90.4% and 87.2%. Based on the results of the study it can be concluded that the learning media based on the Classdojo application on the material of adaptation and mitigation of disasters in class XI SMA Negeri Negeri Negeri 1. mitigation material in class XI SMA Negeri 1 Tilango is very feasible to be applied in geography learning. geography learning.